Secondary School Students’ LLL Competencies, and Their Relation with Classroom Structure and Achievement - Klug, Julia; Lüftenegger, Marko; Bergsmann, Evelyn; Spiel, Christiane; Schober, Barbara (Frontiers in Psychology, 2016)
There is a strong urge to foster lifelong learning (LLL) competencies with its key components - motivation and self-regulated learning - from early on in the education system. School in general is presently not considered to be successful in systematically imparting motivation and self-regulated learning strategies. There is strong evidence that decisive motivational determinants decrease the longer students stay in school. At present, the central sources of information about the situation in Austria are international monitoring studies, which only examine selected aspects of specific target groups, and their interpretability concerning mean values is constricted due to cultural differences. Thus, it is important to conduct additional and more differentiated national surveys of the actual state. This is why this study aimed at answering the following questions: (1) how well are Austrian students equipped for the future, in terms of their lifelong learning competencies, (2) can perceived classroom structure predict students’ LLL, and (3) is there a correlation of students’ LLL with their achievement in the school subjects math and German language. 5366 students (52.1% female) from Thirty-six Austrian schools took part in the online-questionnaire (mean age 15.35 years, SD=2.45), which measured their perceived LLL competencies in the subjects math and German language, their perceived classroom structure and their achievement. Results showed that the great majority of Austrian students – independent from domain and sex - know and are able to apply cognitive as well as metacognitive learning strategies. With regard to motivation the picture is less satisfactory: whilst students’ self-efficacy is not the problem, there is a lack of interest in the school subjects and they often report to follow performance approach goals. Classroom structure positively predicted students’ goals, interest, self-efficacy and learning strategies. Self-efficacy, performance approach goals, meta-cognitive and deep learning strategies in turn predicted achievement positively, and performance avoidance goals negatively.